PENGARUH PUTARAN MESIN TERHADAP EMISI GAS BUANG HIDROKARBON (HC) DAN KARBON MONOKSIDA (CO) - Fernandez, Donny (Lembaga Penelitian Universitas Negeri Padang, 2009)
Result of research indicate that at level of significanti 5%, (1) machine rotation have an effect on significant to gas emission throw away HC with percentage of contribution 98,90%. Where its tendency of machine rotation excelsior hence gas emission throw awayÂ HC progressively. Gas emission throw awayÂ the lowest HC obtained by rotation 2200 that is 153 ppm. (2) Machine rotation have an effect on significant to gas emission throw away CO with percentage of contribution 91,60%. Where its tendency of machine rotation excelsior hence gas emission throw away CO progressively. Gas emission throw away the lowest CO obtained by rotation 1800 that is 0,20%. Keywords : machine rotation, gas emission, hidrocarbon (HC), carbon monoksida (CO)